2020
DOI: 10.1007/s00038-020-01519-8
|View full text |Cite
|
Sign up to set email alerts
|

If I tweet will you cite later? Follow-up on the effect of social media exposure on article downloads and citations

Abstract: Objectives We previously reported that random assignment of scientific articles to a social media exposure intervention did not have an effect on article downloads and citations. In this paper, we investigate whether longer observation time after exposure to a social media intervention has altered the previously reported results. Methods For articles published in the International Journal of Public Health between December 2012 and December 2014, we updated article download and citation data for a minimum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Использование социальных сетей содействует непрерывному профессиональному развитию и презентации результатов профессиональной деятельности профессорско-преподавательского состава [Klein, Niebuhr, D'Alessandro, 2013]. Среди исследователей получает широкое распространение практика размещения в персональных аккаунтах отсылки к полным текстам научных статей [Ibrahim, 2018;Johannsson, Selak, 2020], что позитивно отражается на показателях цитирования научных работ пользователя [Tonia et al, 2020;Kunze et al, 2020]. Отдельного исследовательского интереса заслуживает рассмотрение возможностей для женщин в профессиональном академическом развитии [Lozano Cabezas, Iglesias Martínez, Martínez Ruiz, 2014].…”
Section: литературный обзорunclassified
“…Использование социальных сетей содействует непрерывному профессиональному развитию и презентации результатов профессиональной деятельности профессорско-преподавательского состава [Klein, Niebuhr, D'Alessandro, 2013]. Среди исследователей получает широкое распространение практика размещения в персональных аккаунтах отсылки к полным текстам научных статей [Ibrahim, 2018;Johannsson, Selak, 2020], что позитивно отражается на показателях цитирования научных работ пользователя [Tonia et al, 2020;Kunze et al, 2020]. Отдельного исследовательского интереса заслуживает рассмотрение возможностей для женщин в профессиональном академическом развитии [Lozano Cabezas, Iglesias Martínez, Martínez Ruiz, 2014].…”
Section: литературный обзорunclassified
“…A randomized trial on articles receiving SoMe exposure from Circulation showed no increase on the article page view [5] , [9] . Also studies outside the cardiovascular field could not confirm a significant effect of SoMe exposure on traditional metrics as article citation rates [7] , [10] . or demonstrated only very weak associations [11] , [12] , [13] .…”
mentioning
confidence: 92%
“…This study indicated that academic libraries' tweets were of interest to intermediaries and key role players in the academic field such as university organizations, local public organizations, and information professions. Also within this information-theoretic focus, it's meaningful to note many journals are reporting the "Altmetric"-a measure of the social media reach specifically of published papers [see Publons, for example, and Tonia et al (2020)]. The possibility of Twitter being implemented as a more serious contender as an academic social network space, is therefore likely and potentially exciting [see also Ngai et al (2015)], with particular emphasis by McPherson et al (2015) on Twitter as an informal learning space.…”
Section: Introductionmentioning
confidence: 99%